Comparison of rheological properties and compatibility of asphalt modified with various polyethylene. Issue 1 (2nd January 2021) - Liang, Ming; Xin, Xue; Fan, Weiyu; Zhang, Jizhe; Jiang, Hongguang; Yao, Zhanyong
ABSTRACT: Polyethylene-based modification for asphalt is more and more widely used in paving engineering to deal with growing rutting distress on road pavement. The internal structure of polyethylene (PE) and the resulting asphalt are of interest due to their great influences on performance of pavement. This study investigated the correlation between polyethylene structure and asphalt performance. The polyethylene considered in this paper incorporates high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE). The influence of various PEs on rheological properties of asphalt was investigated by SHRP (Strategic Highway Research Program) method. Compatibility was also evaluated by rheological criterion and microscopic characterisation. The results indicated that modulus, G*/sinδ and viscosity of MDPE modified asphalt are largest among studied samples and it is a good choice for asphalt modification from the perspective of rutting resistance. LLDPE modified asphalt showed the preferable low temperature performance and LDPE is most compatible with asphalt. Higher branched degree of PE improves the low temperature performance of asphalt, but it reduces high temperature performance. A reduction in MFI (melt flow index) facilitates improvement of rutting resistance performance. Unfortunately, low MFI makes PE difficult to be dispersed and leads to poor compatibility with asphalt.